Public Services Delivery in Local Government: Anthropological Insights On State-Citizens Relationship - Poudel, Jiban M.; Sharma, Hament (Nepalese Journal of Development and Rural Studies, 2023)
This paper describes the relationship between the state and the people in relation to public services deliveryby the local government to its citizens in the Federal State of Nepal. The study was based on studied between the years 2019 to 2023 through the ethnographic approach like interviews, observation, and focus group discussions. The data presented in the text reveal that the local government isneithercloser to its citizens, although it is geographically near to them, nor equally access to all of them. It always represents the elite class and powerful group in a society. Furthermore, local government is not both an ‘object’ defined by its territorial boundaries and a ‘concrete structure’ like organography. For the citizens, the state is defined by its activities or performances, including the delivery of services to its citizens.It is constructed through the interaction between the local government and citizens in everyday life experiences that helps us to understand what the local government (state) means for the people at large, and how they perceive it. Furthermore, the understanding of the delivery of public services by local government is possible through the combination of structure and agency together that creates a robust framework for the ethnography of the state.